Collective Forest Creation for Rural Development - a Concept Paper - Upadhyay, D. K.; Yadav, S. P. (Indian Forester, 1999)
Collective forests creation technique can be successfully utilised in bringing non-forest areas for example village common lands etc. under tree cover by combining agriculture and forestry. This will result in development and eco-restoration of the rural areas. Wastelands can also be brought under CFC and this will increase Gross National Product by bringing new areas under food production. It can become tool of common property resource and wasteland development on sustainable basis by providing only one time investment.